2022
DOI: 10.17085/apm.21107
|View full text |Cite
|
Sign up to set email alerts
|

Two-level bilateral ultrasound-guided erector spinae plane block for kyphosis corrective surgery - A case report -

Abstract: Background: Ultrasound-guided erector spinae plane (ESP) block has been used to provide lumbar analgesia. The craniocaudal spread of local anesthetic in this block can be unpredictable in patients with kyphosis due to backward curvature of the spine, which might prevent longitudinal spread. Case: This is a case of a 33-year-old male (60 kg) diagnosed with type 3b kyphosis of the thoracolumbar region at the level of L1 who underwent extended pedicle subtraction osteotomy. ESP block was administered at two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The result showed that the twolevel ESP block provided a better pain sensorial blockage. Similar to our study, Silnha et al (24) found that the two-level ESP block resulted in a better cranio-caudal spread of LA in a patient undergoing kyphosis correction surgery. The spread of LA after the ESP block may follow different pathways, such as between the transverse process and the erector spinae muscle, between the QL muscle and the psoas muscle, and between the QL and the erector spinae muscle, which could block both the ventral and the dorsal rami of the spinal nerve (25).…”
Section: Discussionsupporting
confidence: 91%
“…The result showed that the twolevel ESP block provided a better pain sensorial blockage. Similar to our study, Silnha et al (24) found that the two-level ESP block resulted in a better cranio-caudal spread of LA in a patient undergoing kyphosis correction surgery. The spread of LA after the ESP block may follow different pathways, such as between the transverse process and the erector spinae muscle, between the QL muscle and the psoas muscle, and between the QL and the erector spinae muscle, which could block both the ventral and the dorsal rami of the spinal nerve (25).…”
Section: Discussionsupporting
confidence: 91%
“…[ 9 ] Another case report of a patient who underwent kyphosis correction observed low pain scores until 48 hours for whom ESPB was performed at T12 and L3 (above and below the angle of kyphosis respectively). [ 10 ] Based on these reports, bi-level ESPB would be a better option if the surgery involves multiple levels. This is especially true in the background of the “cranio-caudad spread” of the injectate after ESPB being highly variable[ 6 ] as mentioned earlier.…”
Section: Single-level Versus Bi-level Espb In Spine Surgeriesmentioning
confidence: 99%